Новые клещи-фитосейиды (Parasitiformes, Phytoseiidae) Молдавии - Колодочка, Л.А. (Вестник зоологии, 1980)
Twenty-two species of phytoseiid mites are recorded for the first time from the Moldavian SSR. Some date notes on their distribution and habitat are given. Two new species, Seiulus pecularis sp. n. and Amblyseius kodryensis sp. n. are illustrated and described.